Resonance Frequency Response of Quartz Crystal Microbalance with Different Metal Electrodes in Saccharide Solutions - Abdul Aziz, Siti Salmiwati (2008)
This project investigated the resonance frequency response of Quartz Crystal Microbalance (QCM) with different metal electrodes in different type of liquids. The study investigates the relationship of the density and viscosity of the solutions as a function of the resonance frequency shift (ΔFw) of the QCMs. The technique used was based on the principle of electromechanical coupling of piezoelectric Quartz Crystal Microbalance. In this study, QCMs of 10 MHz fundamental frequency with chromium, molybdenum, tungsten and gold electrodes were used to measure their ΔFw in saccharide solutions. The quartz crystal was clamped between two O-rings in a liquid flow cell. Only one side of the crystal was exposed to the solutions which flow through it propelled by a micro-tube pump. A total of six different saccharide solutions were chosen. The saccharide samples (glucose, fructose, mannose, sucrose, maltose and lactose) were prepared as solutions with different concentrations. All the measurements were carried out at room temperature, 26.5 ± 0.5 °C. The research demonstrates that the interaction of the vibrating quartz crystal with the liquid medium is expressed by a decrease in the resonance frequency, which is proportional to the product of the square root of the solution viscosity and density. The increase in the viscosity of the liquid also causes the vibrating mass to increase on the quartz crystal surface, and this make resonance frequency decreases. The aim of the study was to achieve an understanding of the information provided by measuring the shifts in the resonance frequency of the QCM with different metal electrodes (Cr, Mo, W, and Au) in saccharide solutions. Resonance frequency shift (ΔFw) of the QCM with gold electrodes was found more responsive compared to chromium, molybdenum and tungsten electrodes in saccharide solutions. The determination of parameter K, the coefficient of the equation that governs the relationship between ΔFw , viscosity and density is one of the major objectives of the project. It was found that value K changes with different saccharide solutions in the range of 0.647x104-3.234x104 cm2 g-1 s-1/2.